SQL Demystified - Oppel, Andrew (McGraw-Hill Companies, 2011)
SQL Demystified explains how to use SQL (Structured Query Language)--the ubiquitous programming language for databases. Readers will learn to create database objects, add and retrieve data from a database, and modify existing data. This self-teaching guide comes complete with key points, background information, quizzes at the end of each chapter, and even a final exam. Simple enough for beginners but challenging enough for advanced students, this is a lively and entertaining brush-up, introductory text, or classroom supplement.